2021
DOI: 10.1002/lio2.660
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to apolipoprotein A‐I ratio as an independent indicator of locally advanced nasopharyngeal carcinoma

Abstract: Purpose: To explore the peripheral blood cells (neutrophil/monocyte/lymphocyte/ platelet) to apolipoprotein AI or high-density lipoprotein-cholesterol ratio (NAR, MAR, LAR, PAR, NHR, MHR, LHR, and PHR) as independent prognostic indicators for stage III nasopharyngeal carcinoma (NPC).Patients and methods: Between 2009 and 2014, 562 patients diagnosed with stage III NPC who were treated with a concomitant chemotherapy and intensitymodulated radiotherapy with cumulative cisplatin dose ≥200 mg/m 2 were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…NAR has a predictive value for long-term tumour disease prognosis [ 15 , 35 ]. However, data on NAR’s impact on the long-term prognosis of AF patients are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAR has a predictive value for long-term tumour disease prognosis [ 15 , 35 ]. However, data on NAR’s impact on the long-term prognosis of AF patients are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil-to-apolipoprotein A1 (NAR) ratio is a composite inflammation and lipid metabolism marker that can exert anti-inflammatory and antithrombotic effects [ 12 , 13 , 14 ]. NAR can be used as a prognostic indicator of the five-year overall survival of nasopharyngeal carcinoma patients [ 15 ]. Nevertheless, the relationship between NAR and all-cause and cardiovascular mortality in elderly AF patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Li etc. concluded that NLR could be an attractive indicator for evaluating the 5-year OS in NPC patients with stage III [ 22 ]. High PLR was associated with poor OS in NPC patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses revealed that high ApoA-I level was significantly associated with prolonged OS. Li et al discovered that elevated ApoA-I inhibits the movement and invasion of neutrophils at tumor sites rich in chronic inflammatory factors, thereby reducing the number of neutrophils infiltrating tumor tissue and ultimately increasing the survival rate [ 12 ]. Increasing ApoA-I levels by ApoA-I transgenic mice expression inhibited lymphocyte activation, decreased germinal center B cell numbers at length, and ameliorated glomerulonephritis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have discussed the anti-inflammatory and antitumor properties of ApoA-I, neutrophils, and lymphocytes. For instance, it was discovered that neutrophils would adhere to tumor cells if they overexpressed CD11b and intercellular adhesion molecule 1, but that ApoA-I would remove these molecules [ 12 ]. ApoA-I can also inhibit inflammation in hypercholesterolemic mice by reducing cholesterol accumulation in lymphocytes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%